Job Seekers’ Perceptions of Online E-Recruitment Portals in Mnquma Municipality, South Africa - Pangwa, Nocwaka; Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
This study aims to explore the perceptions of job seekers on government e-recruitment systems. It examines how these digital platforms influence job search experiences and outcomes. A qualitative research methodology was employed for this investigation. This research adopts a case study approach, which facilitates a thorough and multifaceted exploration of complex issues within contexts. The focus of this study is on the Mnquma Local Municipality, with a sample comprising participants drawn from this municipality. Through interviews, the study gathers insights on the usability, accessibility, and effectiveness of e-recruitment from the perspective of diverse job seekers. Key findings reveal that while many appreciate the convenience and transparency of online applications, concerns about the complexity of the systems and the lack of personalized support persist. The key recommendations were to enhance user experience, provide clear guidance, align objectives and outcomes, develop a strong legal and institutional framework, ensure accountability and monitoring.